Ectopic expression of RNF168 and 53BP1 increases mutagenic but not physiological non-homologous end joining. Issue 10 (27th April 2015) - Zong, Dali; Callén, Elsa; Pegoraro, Gianluca; Lukas, Claudia; Lukas, Jiri; Nussenzweig, André
Abstract: DNA double strand breaks (DSBs) formed during S phase are preferentially repaired by homologous recombination (HR), whereas G1 DSBs, such as those occurring during immunoglobulin class switch recombination (CSR), are repaired by non-homologous end joining (NHEJ). The DNA damage response proteins 53BP1 and BRCA1 regulate the balance between NHEJ and HR. 53BP1 promotes CSR in part by mediating synapsis of distal DNA ends, and in addition, inhibits 5' end resection. BRCA1 antagonizes 53BP1 dependent DNA end-blocking activity during S phase, which would otherwise promote mutagenic NHEJ and genome instability. Recently, it was shown that supra-physiological levels of the E3 ubiquitin ligase RNF168 results in the hyper-accumulation of 53BP1/BRCA1 which accelerates DSB repair. Here, we ask whether increased expression of RNF168 or 53BP1 impacts physiological versus mutagenic NHEJ. We find that the anti-resection activities of 53BP1 are rate-limiting for mutagenic NHEJ but not for physiological CSR. As heterogeneity in the expression of RNF168 and 53BP1 is found in human tumors, our results suggest that deregulation of the RNF168/53BP1 pathway could alter the chemosensitivity of BRCA1 deficient tumors.